2022
DOI: 10.1177/00031348221087923
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-Assisted Transversus Abdominis Plane Block Is Superior to Port Site Infiltration in Reducing Post-Operative Opioid Use in Laparoscopic Surgery

Abstract: Background: The ultrasound-guided transversus abdominis plane (TAP) block can be time-consuming, costly, and technically challenging in the bariatric patient population. Laparoscopic-assisted TAP (L-TAP) block was developed and has been shown to be non-inferior to ultrasound-guided blocks. Postoperative pain can be significant, and pain control in the morbidly obese patients can be challenging. This study's aim was to compare L-TAP block to traditional port site infiltration in terms of postoperative opioid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…However, the US may not be a potential option in all medical centers; hence, LAP guidance may serve as an alternative where surgeons can apply the block without depending on the US using a LAP camera [46]. Moreover, Seiler et al [47] reported a significant reduction in IV opioid use postoperatively in the LTAP group compared with the control group in all postoperative measurements for morbidly patients with obesity after LAP Roux-en-Y gastric bypass surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, the US may not be a potential option in all medical centers; hence, LAP guidance may serve as an alternative where surgeons can apply the block without depending on the US using a LAP camera [46]. Moreover, Seiler et al [47] reported a significant reduction in IV opioid use postoperatively in the LTAP group compared with the control group in all postoperative measurements for morbidly patients with obesity after LAP Roux-en-Y gastric bypass surgery.…”
Section: Discussionmentioning
confidence: 99%